Generation of a human X-derived minichromosome using telomere-associated chromosome fragmentation. - Farr, C J (1995)
A linear mammalian artificial chromosome vector will require at least three functional elements: a centromere, two telomeres and replication origins. One route to generate such a vector is by the fragmentation of an existing chromosome. We have previously described the use of cloned telomeric DNA to generate and stably rescue truncated derivatives of a human X chromosome in a somatic cell hybrid. Further rounds of telomere-associated chromosome fragmentation have now been used to engineer a human X-derived minichromosome. This minichromosome is estimated to be < 10 Mb in size. In situ hybridization and molecular analysis reveal that the minichromosome has a linear structure, with two introduced telomere constructs flanking a 2.5 Mb alpha-satellite array. The highly truncated chromosome also retains some chromosome-specific DNA, originating from Xp11.21. There is no significant change in the mitotic stability of the minichromosome as compared with the X chromosome from which it was derived.